Molecular characterisation of tagO-deficient mutants of Staphylococcus aureus - Carvalho, Joana (Trinity College (Dublin, Ireland). Department of Microbiology, 2017)
Wall teichoic acid (W TA) is a major component of the Gram -positive bacterial cell wall. Despite not being essential, it plays important roles in cell growth, division, morphology and virulence. The enzyme TagO initiates the assembly of W TA. Here, isogenic tagO mutants of methicillin sensitive and methicillin resistant strains of S. aureus were generated. All mutants failed to produce W TA. RNA-seq was carried out to investigate transcriptional changes in a tagO mutant of strain New man. The lack of tagO caused the up-regulation of 107 genes and the down-regulation of 85 genes compared to the wild-type. Genes from the cell wall stress stimulon and genes responsible for capsule production (cap operon) were up-regulated. While genes involved in virulence and colonisation, such as the agr system (the main accessory regulatory system that controls virulence factors) spa and clfB were down-regulated. These changes in gene expression were confirmed using qRT-PCR.
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2017